Emotional skills and health assessment in interventions for intimate partner violence perpetrators: A systematic review of randomized controlled trials - Miguel Mora-Pelegrín; María Aranda; Beatriz Montes-Berges (PLoS ONE, 2025)
The present study had two objectives: 1) To analyze the effectiveness of intervention programs for intimate partner violence (IPV) perpetrators that include learning emotional skills; and 2) to examine whether these programs assess variables related to the health and well-being of IPV perpetrators as a result of the intervention, and whether the obtained personal benefits are leveraged to enhance motivation towards therapy. This systematic review was carried out following the PRISMA guidelines. PsycINFO, PubMed, Scopus and PsycARTICLES databases were searched for articles published between January 2000 and December 2023, in order to identify randomized controlled trials of interventions for IPV perpetrators that included learning emotional skills, and that considered the health and well-being of the participants as motivational aspects in therapy. Fifteen primary studies that met the selection and eligibility criteria were included. The results indicated that slightly over half of the intervention programs for IPV perpetrators who develop emotional competencies were more effective in reducing recidivism and improving variables associated with this type of violence than were those that did not include this type of learning (53% of the trials showed significant differences in favor of the intervention groups). In addition, it became evident that the personal benefits obtained by the participants during therapy, which are related to their health and degree of well-being, are barely considered in efforts to improve motivational strategies. These results have important practical implications: firstly, they allow adjusting the contents of intervention programs for IPV perpetrators more effectively and, secondly, they add new elements that help the participants to improve their motivation and adherence to therapy.